Combination of Lidocaine and IL-1Ra Is Effective at Reducing Degradation of Porcine Cartilage Explants. Issue 7 (June 2022) - Buchanan, Michael W.; Furman, Bridgette D.; McNulty, Amy L.; Olson, Steven A.
Background: Posttraumatic inflammation after joint injury, ranging from sprains to articular fracture, contributes to the development of arthritis, and the administration of interleukin 1 (IL-1) receptor antagonist (IL-1Ra) is a potential intervention to mitigate this response. Although IL-1Ra mitigates cartilage degenerative changes induced by IL-1, lidocaine is used for local pain management in acute joint injury. Intra-articular delivery of both drugs in combination would be a novel and possibly disease–modifying treatment. However, it is not known whether the interaction with lidocaine at clinical concentrations (1%) would alter the efficacy of IL-1Ra to protect cartilage from the catabolic effects of IL-1. Hypothesis: Treatment of articular cartilage with IL-1Ra in combination with a clinically relevant concentration of lidocaine (1%) will inhibit the catabolic effects of IL-1α in a manner similar to treatment with IL-1Ra alone. Study Design: Controlled laboratory study. Methods: Fresh porcine cartilage explants were harvested, challenged with IL-1α, and incubated for 72 hours with IL-1Ra or a combination of IL-1Ra and lidocaine. The primary outcome was total sulfated glycosaminoglycan (sGAG) release. Additional experiments assessed the effect of storage temperature and premixing of IL-1Ra and lidocaine on sGAG release. All explants were histologically assessed for cartilage degradation using a modified Mankin grading scale. Results: The combination of IL-1Ra and lidocaine, premixed at various time points and stored at room temperature or 4°C, was as effective as IL-1Ra alone at inhibiting IL-1α–mediated sGAG release. Mankin histopathology scores supported these findings. Conclusion: Our hypothesis was supported, and results indicated that the combination of IL-1Ra and lidocaine was as efficacious as IL-1Ra treatment alone in acutely mitigating biological cartilage injury due to IL-1α in an explant model. Clinical Significance: The combination of IL-1Ra and lidocaine is stable when reagents are stored in advance of administration at varying temperatures, providing clinically relevant information about storage of medications. The ability to premix and store this drug combination for intra–articular delivery may provide a novel treatment after joint injury to provide pain relief and block inflammation–induced catabolism of joint tissues.